PENGEMBANGAN MODEL PENDIDIKAN KARAKTER PEDULI SOSIAL MELALUI METODE BERMAIN PERAN DI TK TUNAS MEKAR INDONESIA BANDAR LAMPUNG - Agung, Putry; Asmira, Yulistyas Dwi (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
ABSTRACTCharacter education is very necessary for the realization of national education goals. Over time, it is necessary to instill social caring character education since early age is a very important period of development in human life. Thus it is necessary to develop socially caring character education through learning role playing methods. The purpose of this study is to; Developing a character education model through the role playing method in TK Tunas Mekar Indonesia (TMI) Bandar Lampung. This study uses research and development methods with the following steps; (a) needs analysis, (b) planning includes compiling RPPM and RPPH (c) determining elements of character education; (d) collect learning material; (e) compile a model draft, (f) validation, (g) model revision, (h) model trial; and (i) product improvement. Data collection instruments used are; (1) questionnaire, (2) discussion, (3) interview. The data analysis technique that is carried out is quantitative descriptive analysis and qualitative descriptive analysis. This research produced a social caring character education model.Keywords: Character Education Model, Social Care, Role Playing.